Rohdea fargesii, the correct name for Rohdea chinensis (Asparagaceae) - Deng, Yunfei (Phytotaxa, 2017)
The genus Rohdea Roth (1821: 196) (Asparagaceae) was established with a sole species R. japonica (Thunb. in Murray 1784: 340) Roth (1821: 196). It was recognized as a monospecific genus for long time (Wang & Tang 1978, Liang & Tamura 2000). The evidence from molecular analyses revealed that Campylandra Backer (1875: 582) might be merged with Rohdea (Yamashita & Tamura 2000, 2004). Tanaka (2003) and Yamashita & Tamura (2004) formally merged Campylandra with Rohdea and led the latter a genus including 17 species distributed in East Asia.